A Novel Stress Echocardiography Pattern for Myocardial Bridge With Invasive Structural and Hemodynamic Correlation. Issue 2 (16th April 2013) - Lin, Shin; Tremmel, Jennifer A.; Yamada, Ryotaro; Rogers, Ian S.; Yong, Celina Mei; Turcott, Robert; McConnell, Michael V.; Dash, Rajesh; Schnittger, Ingela
Abstract : Background: Patients with a myocardial bridge (MB) and no significant obstructive coronary artery disease (CAD) may experience angina presumably from ischemia, but noninvasive assessment has been limited and the underlying mechanism poorly understood. This study seeks to correlate a novel exercise echocardiography (EE) finding for MBs with invasive structural and hemodynamic measurements. Methods and Results: Eighteen patients with angina and an EE pattern of focal end‐systolic to early‐diastolic buckling in the septum with apical sparing were prospectively enrolled for invasive assessment. This included coronary angiography, left anterior descending artery (LAD) intravascular ultrasound (IVUS), and intracoronary pressure and Doppler measurements at rest and during dobutamine stress. All patients were found to have an LAD MB on IVUS. The ratios of diastolic intracoronary pressure divided by aortic pressure at rest (Pd/Pa) and during dobutamine stress (diastolic fractional flow reserve [dFFR]) and peak Doppler flow velocity recordings at rest and with stress were successfully performed in 14 patients. All had abnormal dFFR (≤0.75) at stress within the bridge, distally or in both positions, and on average showed a more than doubling in peak Doppler flow velocity inside the MB at stress. Seventy‐five percent of patients had normalization of dFFR distal to the MB, with partial pressure recovery and a decrease in peak Doppler flow velocity. Conclusions: A distinctive septal wall motion abnormality with apical sparing on EE is associated with a documented MB by IVUS and a decreased dFFR. We posit that the septal wall motion abnormality on EE is due to dynamic ischemia local to the compressed segment of the LAD from the increase in velocity and decrease in perfusion pressure, consistent with the Venturi effect.